2022
DOI: 10.1002/acr2.11424
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Major Adverse Cardiac Events in Patients With Systemic Lupus Erythematosus

Abstract: Objectives Patients with systemic lupus erythematosus (SLE) have a high risk of cardiovascular disease that could potentially increase postoperative major adverse cardiac events (MACE). We determined the rate of MACE in patients with SLE undergoing noncardiac surgery using national claims‐based data. Methods This was a retrospective cohort study using Optum Clinformatics Data Mart from 2007 to 2020. We identified a cohort of patients with SLE who had undergone noncardiac surgeries using Current Procedural Term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although these data suggest concerns for care quality via telehealth for patients with SLE and IA, a retrospective analysis from a large Texas health care system reported that lupus patients with lower socioeconomic status missed fewer telehealth appointments compared with F2F visits, indicating that telehealth options may maintain attendance, an aspect of care quality. 17 Taken together, these studies suggest that telehealth may be less suitable for new patients with possible IA or autoimmune CTD, although it may be suitable to enhance continuity of care during follow‐up of patients with IA and SLE and may also be appropriate to provide osteoporosis care. 13 , 14 …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Although these data suggest concerns for care quality via telehealth for patients with SLE and IA, a retrospective analysis from a large Texas health care system reported that lupus patients with lower socioeconomic status missed fewer telehealth appointments compared with F2F visits, indicating that telehealth options may maintain attendance, an aspect of care quality. 17 Taken together, these studies suggest that telehealth may be less suitable for new patients with possible IA or autoimmune CTD, although it may be suitable to enhance continuity of care during follow‐up of patients with IA and SLE and may also be appropriate to provide osteoporosis care. 13 , 14 …”
Section: Resultsmentioning
confidence: 97%
“…Two were prospective cohort studies from Italy 11 and the US, 12 and five were retrospective studies from the UK, 13 , 14 Australia, 15 and the US. 16 , 17 All were single‐center studies conducted after March 2020. The optimal screening method for telehealth visit appropriateness was addressed in two studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation